Lactobacillus plantarum -derived Extracellular Vesicles Protect Atopic Dermatitis Induced by Staphylococcus aureus -derived Extracellular Vesicles - Kim, Min-Hye; Choi, Seng Jin; Choi, Hyun-Il; Choi, Jun-Pyo; Park, Han-Ki; Kim, Eun Kyoung; Kim, Min-Jeong; Moon, Byoung Seok; Min, Taek-ki; Rho, Mina; Cho, Young-Joo; Yang, Sanghwa; et al. (Allergy, asthma & immunology research, 2018)
The microbial environment is an important factor that contributes to the pathogenesis of atopic dermatitis (AD). Recently, it was revealed that not only bacteria itself but also extracellular vesicles (EVs) secreted from bacteria affect the allergic inflammation process. However, almost all research carried out so far was related to local microorganisms, not the systemic microbial distribution. We aimed to compare the bacterial EV composition between AD patients and healthy subjects and to experimentally find out the beneficial effect of some bacterial EV composition. Twenty-seven AD patients and 6 healthy control subjects were enrolled. After urine and serum were obtained, EVs were prepared from samples. Metagenomic analysis of 16s ribosomal DNA extracted from the EVs was performed, and bacteria showing the greatest difference between controls and patients were identified. In vitro and in vivo therapeutic effects of significant bacterial EV were evaluated with keratinocytes and with Staphylococcus aureus-induced mouse AD models, respectively. The proportions of Lactococcus, Leuconostoc and Lactobacillus EVs were significantly higher and those of Alicyclobacillus and Propionibacterium were lower in the control group than in the AD patient group. Therefore, lactic acid bacteria were considered to be important ones that contribute to the difference between the patient and control groups. In vitro, interleukin (IL)-6 from keratinocytes and macrophages decreased and cell viability was restored with Lactobacillus plantarum-derived EV treatment prior to S. aureus EV treatment. In S. aureus-induced mouse AD models, L. plantarum-derived EV administration reduced epidermal thickening and the IL-4 level. We suggested the protective role of lactic acid bacteria in AD based on metagenomic analysis. Experimental findings further suggest that L. plantarum-derived EV could help prevent skin inflammation.